Both Memory and CD45RA(+)/CD62L(+) Naive CD4(+) T Cells Are Infected in Human Immunodeficiency Virus Type 1-Infected Individuals - Ostrowski, Mario A. (American Society for Microbiology, 1999)
Cellular activation is critical for the propagation of human immunodeficiency virus type 1 (HIV-1) infection. It has been suggested that truly naive CD4(+) T cells are resistant to productive HIV-1 infection because of their constitutive resting state. Memory and naive CD4(+) T-cell subsets from 11 HIV-1-infected individuals were isolated ex vivo by a combination of magnetic bead depletion and fluorescence-activated cell sorting techniques with stringent criteria of combined expression of CD45RA and CD62L to identify naive CD4(+) T-cell subsets. In all patients HIV-1 provirus could be detected within naive CD45RA(+)/CD62L(+) CD4(+) T cells; in addition, replication-competent HIV-1 was isolated from these cells upon CD4(+) T-cell stimulation in tissue cultures. Memory CD4(+) T cells had a median of fourfold more replication-competent virus and a median of sixfold more provirus than naive CD4(+) T cells. Overall, there was a median of 16-fold more integrated provirus identified in memory CD4(+) T cells than in naive CD4(+) T cells within a given patient. Interestingly, there was a trend toward equalization of viral loads in memory and naive CD4(+) T-cell subsets in those patients who harbored CXCR4-using (syncytium-inducing) viruses. Within any given patient, there was no selective usage of a particular coreceptor by virus isolated from memory versus naive CD4(+) T cells. Our findings suggest that naive CD4(+) T cells may be a significant viral reservoir for HIV, particularly in those patients harboring CXCR4-using viruses.